Moving beyond disrespect and abuse: addressing the structural dimensions of obstetric violence - Sadler, M.; Santos, M. J.; Ruiz-Berdún, D.; Rojas, G. L.; Skoko, E.; Gillen, P.; Clausen, J. A. (Reproductive Health Matters, 2016)
During recent decades, a growing and preoccupying excess of medical interventions during childbirth, even in physiological and uncomplicated births, together with a concerning spread of abusive and disrespectful practices towards women during childbirth across the world, have been reported. Despite research and policy-making to address these problems, changing childbirth practices has proved to be difficult. We argue that the excessive rates of medical interventions and disrespect towards women during childbirth should be analysed as a consequence of structural violence, and that the concept of obstetric violence, as it is being used in Latin American childbirth activism and legal documents, might prove to be a useful tool for addressing structural violence in maternity care such as high intervention rates, non-consented care, disrespect and other abusive practices.